The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/app11104519
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Polyunsaturated Fatty Acids against Dry Eye Disease: A Literature Review

Abstract: Dry eye disease (DED) is a common disease, and have an adverse effect the physical, functional, and psychological quality of life. It is a multifactorial disorder characterized by the loss of tear film homeostasis, in which self-perpetuating vicious cycle leads to deterioration of function and inflammation of the lacrimal functional unit. Hence, treatment strategies should be aimed at the interruption of the vicious inflammatory cycle and alleviation of ocular surface inflammation. Anti-inflammatory therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
(184 reference statements)
0
2
0
Order By: Relevance
“…Clinical studies showed that the type of fatty acid intake affects the course of the disease ( Hu et al, 2002 ). As an indispensable part of people’s daily diet, fatty acids have increasingly become the focus of researches ( Manson et al, 2020 ; Farukhi et al, 2021 ; Hyon and Han, 2021 ). n-3 fatty acids are one type of long-chain polyunsaturated fatty acids (LCPUFAs).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies showed that the type of fatty acid intake affects the course of the disease ( Hu et al, 2002 ). As an indispensable part of people’s daily diet, fatty acids have increasingly become the focus of researches ( Manson et al, 2020 ; Farukhi et al, 2021 ; Hyon and Han, 2021 ). n-3 fatty acids are one type of long-chain polyunsaturated fatty acids (LCPUFAs).…”
Section: Introductionmentioning
confidence: 99%
“…The number of registered randomized clinical trials about the effect of omega-3 fatty acids in DED (according to the search conducted in January 2024 in the ClinicalTrials.org registry) is 34. The majority of randomized clinical trials that are analyzed in available systematic reviews and/or metaanalysis support the efficacy of omega-3 fatty acid supplementation on the symptoms and progression of DED [34,54,55]. A more recent systematic-review and meta-analysis from 2023, found objective improvement in OSDI but not in other objective measures of DED like Schirmer's test.…”
Section: Systemic Effects Of Omega-3 Fatty Acids In Dry Eye Diseasementioning
confidence: 99%